Interventions for helping people recognise early signs of recurrence in depression - Morriss, Richard K (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The overall aim is to conduct a systematic review of all intervention studies that include systematically teaching the recognition of early warning signs(EWS) of recurrence to people with recurrent depressive disorders and/or their carers.The objectives are: 1. To compare the effectiveness of an EWS intervention plus treatment as usual (TAU) versus TAU not involving a psychological therapy on time to next depressive episode. 2. To compare the effectiveness of an EWS intervention plus TAU versus TAU plus another psychological therapy on time to next depressive episode. 3. To compare the effectiveness of intermittent medication used on recognition of EWS without continuing antidepressant use versus TAU involving continued antidepressant use on time to next depressive episode.